Effects of W/Co co-doping on the structural, multiferroic, dielectric and optical properties of filled tungsten bronze Ba4Sm2Fe2Nb8O30 ceramics - Xuzhong Zuo; Dongpo Song; Yifeng Zheng; Zhenzhen Hui; Teng Guo; Wei Dong; Enjie He; Yanfu Qin; Banggui Guan; Jie Yang; Xuebin Zhu; Jianming Dai (Results in Physics, 2024)
The structural, magnetic, ferroelectric, dielectric, magneto-dielectric and optical properties of W/Co co-substituted tungsten bronze Ba4Sm2Fe2Nb8-3x(W2Co)xO30 (0 ≤ x ≤ 0.3) ceramics were studied in detail. All the samples can be indexed with the tetragonal structure with the space group of P4bm. The room-temperature ferromagnetism with rather high ferromagnetic Curie temperature Tc was obtained in all compositions. The co-doping of W/Co ions obviously optimized the ferromagnetism and ferroelectricity. The composition x  = 0.2 showed a superior multiferroicity with the remnant magnetization Mr of 0.15 emu/g and the remnant polarization Pr of 2.1μC/cm2 as well as the Tc of 886 K. The low-temperature relaxation was related to the thermal process of oxygen vacancies, while the another one around 300 K was ascribed to the localized hopping of electrons. The relative increment of magneto-dielectric constant (MDC) obeyed with the square term of magnetization in Ginzburg-Landau theory, implying the existence of intrinsic magneto-electric coupling effect. A relatively large MDC of 0.17 % was achieved in pure sample. In addition, two direct inter-band transitions with the narrow band gaps of ∼2.0 eV and ∼2.5 eV were demonstrated.